(3YeOI GdLQGMjfs - (3jYbhH Hf ESMGb GdeSjMji Gdedcj GdcQcj GHf Gdba, CHh GdaQL,J (B685 (3g` s ((3eMeO Hf Ydi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdNdb HbOQJg hHYO abO GTJci Edi HYV LQGjMjI ReGffG bdI GgJeGe CQHGH gPG Gdaf HCeQ gPg GdUfGYI s
(3BNQgG (B:s
(3hdG jLYd ai TeS MGQI KdGKjf jhekG hjMQc cd jhe hjLYd ai EfGA hjSJYed hGddg JYGdi CYde Je s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI eJhSWI s
(3GdfSNI HgG JdhjK s
Keywords: (3eJaQbGJs